2020
DOI: 10.20473/mbiom.v30i2.2020.45-51
|View full text |Cite
|
Sign up to set email alerts
|

The Profile of Children With Congenital Rubella Syndrome Suffering From Hearing Disorders in Dr. Soetomo General Academic Hospital, Surabaya, Indonesia

Abstract: Background: Congenital Rubella Syndrome (CRS) is an infection that can cause hearing loss which is commonly found in infants in Indonesia. The hearing screening of otoacoustic emission (OAE) and automated auditory brainstem response (AABR) is essential as an early screening to prevent speech and language development disorders which may reduce the social function of the patient in the future. Objective: To analyze the profile of children with CRS who suffer from hearing loss in Dr. Soetomo General Academic Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Board et al quoted by Yudistira reported that hearing loss occurred in 48.5% of all samples with positive serology results. Some of the infants had positive IgM result at the of 0-3 months and then at the age 4-6 months the infants had positive IgG results (Kesuma, et al, 2020) The patients in this study who had pathological findings on MRI and CT scan were still given cochlear implants because they did not contraindicate cochlear implants. Contraindications to cochlear implants include absence of the cochlea or cochlear nerve, and severe mental impairment or mental retardation.…”
Section: Discussionmentioning
confidence: 73%
“…Board et al quoted by Yudistira reported that hearing loss occurred in 48.5% of all samples with positive serology results. Some of the infants had positive IgM result at the of 0-3 months and then at the age 4-6 months the infants had positive IgG results (Kesuma, et al, 2020) The patients in this study who had pathological findings on MRI and CT scan were still given cochlear implants because they did not contraindicate cochlear implants. Contraindications to cochlear implants include absence of the cochlea or cochlear nerve, and severe mental impairment or mental retardation.…”
Section: Discussionmentioning
confidence: 73%
“…Most infants with congenital cytomegalovirus (CMV) infection are asymptomatic at birth but approximately 10 percent have symptoms 1 . A study conducted at the Dr. Soetomo General Academic Hospital found that 64.4% of congenital CMV infection occurred in the 0-3 month age group 2 . CMV belongs to the herpes virus family which includes human herpes virus (HHV), simple herpes virus and the Epstein-Barr virus.…”
Section: Introductionmentioning
confidence: 99%